SIMULATION OF DC-DC CONVERTER SYMBOLIC DYNAMICS: DETECTION AND IDENTIFICATION OF BIFURCATION TYPES - Hamzaoui, Abdelaziz; Ustinov, Pavel; Sholonik, Andrey; Kolokolov, Yury (International Journal of Computing, 2014)
In this paper continuous-time model to discrete-time symbolic model transformation for an algorithmization of the DC-DC buck converter dynamics investigation process is derived. The proposed concept of symbolic index allows evaluate quantitatively the symbolic model change and makes possible the “nonsmooth” bifurcations revealing. The numerical simulation that had been carried out verifies utilizing efficiency of symbolic modeling both as for possible bifurcation pattern forecasting, as for bifurcation type identification.